Epidemiology of Extended Spectrum Beta Lactamase Producing Gram Negative Rods - Rafique, Ayesha; Rasheed, Farhan; Saeed, Muhammad; Hassan, Sajjad; Nadeem, Syeda Fatima; Imran, Ambereen Anwar (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To estimate the distribution of ESBL producing capacity among different Gram negative isolates along with specimen and department wise prevalence in a tertiary care hospital. METHODOLGY: This cross-sectional study was conducted at the Microbiology section of Pathology Department, Allama Iqbal Medical College, Lahore, Pakistan, from August 2016 to January 2017. Total of 437 clinical samples were collected from different wards of Jinnah Hospital, Lahore. Sample was cultured on Blood agar, MacConkey’s agar, chocolate agar, CLED agar. After the identification every Gram negative isolate was further processed for the antibiotic susceptibility testing following Modified Kirby Bauer disc diffusion method. ESBL detection was performed by the combination drugs disc method using ceftriaxone + clavulanic acid (30/10 ?g) in case of Enterobacteriacae, ceftazidime + clavulanic acid (30/10?g) in case of Pseudomonas species. RESULTS: Among total 437 patients male and female were 61% and 39% respectively, overall 21.5% (94/437) were ESBl producers. Distribution of ESBL producers was as followed Acinetobacter spp 22.3% (31/139), Escherichia coli 37.5% (27/72), Klebsiella spp 31.9% (15/47), Pseudomonas aeruginosa 8.4% (13/154) and Proteus spp 32.0% (8/25). Department wise ESBL positivity was as followed Surgical units 25.6% (32/125) Medical unit 31.9% (30/94), Burn centre 10% (8/80), ICU 20% (8/40) Surgical Allied 11.7% (4/34), Medical Allied 6.2% (2/32), Neurology 36.3% (8/22), Gynaecology 28.5% (2/7) and Dermatology 33.3% (1/3). CONCLUSION: High percentage of ESBL positivity seen in Escherichia coli and Proteus spp, among departments neurology and medical unit is holding maximum positivity. High frequency of ESBL producing Gram negative isolates strongly recommend its detection and management accordingly. It can lead to treatment failures in Gram negative rods associated infections.